The lightning rod - Meltzer, Brad (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
When Archie Mint is killed while trying to stop a robbery in his own home, his family learns that his life, so perfect on the surface, held criminal secrets none of them could have imagined.
Sequel to: The escape artist.
Keywords: Undertakers and undertaking -- Fiction; Women artists -- Fiction; Defense information, Classified -- Fiction; Official secrets -- United States -- Fiction; Conspiracies -- United States -- Fiction; Murder -- Investigation -- Fiction; Conspiracies -- Fiction; United States -- Army -- Fiction; Detective and mystery fiction; Thrillers (Fiction)